Silicon-carbon material, preparation method and application thereof, and lithium ion battery
By introducing carbon nanotubes and silicon layers into the silicon-based anode material to form a core-shell structure, the silicon-based anode material is solved, and the problem of insufficient volume effect, compressive resistance and electrical conductivity of the silicon-based anode material in lithium-ion batteries is achieved, and better electrochemical performance is achieved.
Patent Information
- Application Number
- CN202411876419.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
The existing silicon-based anode materials have insufficient volume effects, compressive resistance and electrical conductivity in lithium-ion batteries, which cannot meet the electrochemical performance requirements of the battery.
By carbonizing and activation treatment of the mixture of carbon source and transition metal salt, porous carbon is generated, and carbon nanotubes and silicon layers are grown in situ by chemical vapor deposition method to form a core-shell structure silicon-carbon material embedded in the carbon nanotube.
The conductivity, compressibility and expansion suppression performance of silicon carbon materials are improved, and the prepared lithium-ion battery can take into account excellent first-time, capacity, rate performance and cycle performance.
Smart Images

Figure CN119695114A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-carbon material and a preparation method, application and a lithium-ion battery thereof. Background Art
[0002] With the rapid development of science and technology, advanced devices such as drones, electric vehicles, and smart wearable devices have higher requirements for the lightweight and endurance of lithium-ion batteries. However, commercial graphite anode materials are gradually approaching their theoretical capacity, making it increasingly difficult to increase the energy density of lithium-ion batteries.
[0003] Silicon-based negative electrode materials have attracted widespread attention due to their high capacity, but silicon-based negative electrode materials have a serious volume effect. During the charging and discharging process, the volume of silicon will repeatedly increase or decrease, resulting in huge volume expansion. In addition, the existing silicon-based negative electrode materials have poor compressive resistance and conductivity, and cannot meet the electrochemical performance requirements of the battery. Summary of the invention
[0004] In order to solve the above problems existing in the existing silicon-carbon materials, the present invention provides a silicon-carbon material and its preparation method, application and lithium-ion battery. The silicon-carbon material has good conductivity and compression resistance, and excellent expansion inhibition performance, and the prepared lithium-ion battery can take into account excellent first efficiency, gram capacity, rate performance and cycle performance.
[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions.
[0006] The present invention provides a method for preparing a silicon-carbon material, which comprises the following steps:
[0007] S1, carbonizing and activating a mixture of a carbon source and a transition metal salt to obtain porous carbon;
[0008] S2, performing carbon deposition on the porous carbon by chemical vapor deposition to in-situ grow carbon nanotubes to obtain a first precursor;
[0009] S3, performing silicon deposition on the first precursor by chemical vapor deposition to obtain a second precursor;
[0010] S4, carbon-coating the second precursor; acid-washing and drying to obtain the silicon-carbon material.
[0011] In step S1, the mass ratio of the carbon source to the transition metal salt is preferably 1:(0.01-0.8), more preferably 1:(0.05-0.8), for example 1:0.05, 1:0.3 or 1:0.8.
[0012] In step S1, the transition metal salt may be a transition metal salt conventionally used in the art, preferably including one or more of transition metal nitrates, transition metal sulfates, transition metal phosphates and transition metal borates.
[0013] In some specific embodiments, the transition metal salt comprises nickel nitrate.
[0014] In some specific embodiments, the transition metal salt comprises nickel sulfate.
[0015] In some specific embodiments, the transition metal salt comprises nickel phosphate.
[0016] In some specific embodiments, the transition metal salt comprises nickel borate.
[0017] In some embodiments, the transition metal salt comprises tin nitrate.
[0018] In step S1, the transition metal salt preferably includes one or more of iron salt, nickel salt, cobalt salt, silver salt, gold salt and tin salt, for example, nickel salt or tin salt.
[0019] In step S1, the carbon source can be a conventional carbon source for synthesizing porous carbon in the art, preferably including one or more of resin, sucrose, glucose, fructose, starch, cellulose, triglycerides, fatty acids, hemicellulose, lignin and asphalt, further preferably resin, and more preferably phenolic resin.
[0020] In step S1, the carbonization treatment can be performed under conventional carbonization treatment conditions in the art.
[0021] Wherein, the temperature of the carbonization treatment is preferably 400-800°C.
[0022] The carbonization treatment time is preferably 1-8 h, for example 2 h.
[0023] The heating rate of the carbonization treatment is preferably 1-8°C / min, for example 5°C / min.
[0024] The carbonization treatment is preferably carried out in the following manner: heating to 400-800°C at 1-8°C / min and keeping the temperature for 1-8 h, for example, heating to 800°C at 5°C / min and keeping the temperature for 2 hours.
[0025] In the present invention, in step S1, during the carbonization process, the transition metal salt generates transition metal nanoparticles inside the porous carbon, and then induces in-situ growth of carbon nanotubes during subsequent carbon deposition to form a three-dimensional skeleton network, thereby improving the conductivity, strength and toughness of the silicon-carbon material, and further improving the expansion inhibition performance. In addition, due to the presence of the transition metal, the carbonization process is conducive to the generation of amorphous carbon, which is more easily activated, thereby achieving the generation of controllable pores.
[0026] In step S1, the activation treatment may be performed by an activation treatment method conventionally used in the art, preferably including alkali activation or gas activation; the gas activation is preferably carbon dioxide activation or water vapor activation.
[0027] The gas activation time is preferably 1-8 hours, for example 4 hours.
[0028] Wherein, the temperature of the gas activation is preferably 500-600°C.
[0029] The heating rate of the gas activation is preferably 1-8°C / min, for example 5°C / min.
[0030] The ventilation volume of the gas activation is preferably 1-6 L·min -1 kg -1 , for example, 5 L min -1 kg -1 .
[0031] The gas activation method is preferably: heating to 500-600°C at 1-8°C / min and keeping warm for 1-8 h, for example: heating to 600°C at 5°C / min and keeping warm for 4 hours.
[0032] In some preferred embodiments, in step S1, the activation treatment is carbon dioxide activation, and the gas source for the carbon dioxide activation includes carbon dioxide and an inert atmosphere. The volume ratio of the carbon dioxide to the inert atmosphere is, for example, 4:1. The inert atmosphere is, for example, nitrogen. The temperature is increased to 500-600°C at 1-8°C / min and kept warm for 1-8 h, for example: the temperature is increased to 600°C at 5°C / min and kept warm for 4 hours.
[0033] In step S1, the activation treatment preferably includes a pulverization treatment before the activation treatment; the pulverization treatment preferably includes pulverizing to a Dv50 particle size of 5-15 μm, for example, 8 μm.
[0034] In step S1, the Dv50 particle size of the porous carbon is preferably 5-15 μm, more preferably 7-8 μm, for example, 7.7 μm, 7.8 μm or 7.9 μm.
[0035] In step S1, the specific surface area of the porous carbon is preferably 1200-2500 m 2 / g, more preferably 1800-1950m 2 / g, for example, 1810 m 2 / g, 1854 m 2 / g, 1867 m 2 / g, 1869 m 2 / g, 1876 m 2 / g, 1886 m 2 / g, 1896 m 2 / g or 1945 m 2 / g.
[0036] In step S1, the pore volume of the porous carbon is preferably 0.7-1.5 cm 3 / g, for example, 0.87 cm 3 / g, 0.98cm 3 / g, 1.01 cm 3 / g, 1.05 cm 3 / g, 1.08 cm 3 / g, 1.09 cm 3 / g, 1.1 cm 3 / g or 1.11 cm 3 / g.
[0037] In step S1, the mesopore volume of the porous carbon is preferably 0-20%, preferably 5%-15%, for example, 5.8%, 6.8%, 8.6%, 9.8%, 10.5%, 10.8%, 12.4%, 14.6% or 14.7%, where the percentage is the volume percentage of the total pore volume of the porous carbon.
[0038] In step S1, the micropore volume of the porous carbon is preferably 80-100%, preferably 85%-95%, for example, 85.3%, 85.4%, 87.6%, 89.2%, 89.5%, 90.2%, 91.4%, 93.2% or 94.2%, where the percentage is the volume percentage of the total pore volume of the porous carbon.
[0039] In the present invention, in step S2, the transition metal oxide in the porous carbon can catalyze the in-situ growth of carbon nanotubes. While the carbon nanotubes are grown in-situ, a carbon coating process is carried out simultaneously. At this time, the grown carbon nanotubes can grow in the form of being embedded in the carbon layer, and after protruding out of the carbon layer, it is helpful to carbon coat again, accelerate the coating speed, and thicken the carbon layer. Among them, when the carbon nanotubes are grown in-situ, whether the carbon nanotubes are single-walled carbon nanotubes or multi-walled carbon nanotubes depends on the loading amount of the transition metal, the uniformity of the distribution, and the nano-degree of the transition metal oxide.
[0040] In step S2, the temperature of the carbon deposition is preferably 400-800°C, for example 600°C.
[0041] In step S2, the carbon deposition time is preferably 10-60 min, for example, 30 min;
[0042] In step S2, the carbon source for carbon deposition can be a carbon source conventionally used for chemical vapor deposition in the art, preferably including one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates, more preferably including one or more of methane, ethane, propane, cyclopropane, n-butane, isobutane, n-pentane, neopentane, methyl chloride, ethyl chloride, trifluoromethane, ethylene oxide, acetylene, propyne, butyne, methylacetylene, vinylacetylene and ethylene, for example, methane or acetylene.
[0043] In step S2, during the carbon deposition process, the ventilation rate of the carbon source is preferably 1-8 L·min -1 kg -1 , for example 4L·min -1 kg -1 or 5 L min -1 kg -1 .
[0044] In step S2, the gas source for carbon deposition may further include an inert atmosphere.
[0045] Preferably, the volume ratio of the carbon source for carbon deposition to the inert atmosphere is 1:(0.5-15).
[0046] Preferably, the inert atmosphere comprises one or more of nitrogen, argon and helium.
[0047] Preferably, the ventilation volume of the inert atmosphere is 10-50 L·min -1 kg -1 , for example, 15 L min -1 kg -1 .
[0048] In step S3, the temperature of silicon deposition is preferably 300-1000°C, for example 600°C.
[0049] In step S3, the silicon deposition time is preferably 1-6 hours, for example 3 hours.
[0050] In step S3, the silicon source for silicon deposition can be a silicon source conventionally used for chemical vapor deposition in the art, preferably including one or more of monosilane, disilane, trisilane, dimethylsilane, hexamethyldisilane, dichlorosilane, trichlorosilane, silicon tetrachloride and silicon tetrafluoride, for example, monosilane.
[0051] In step S3, during the silicon deposition process, the ventilation rate of the silicon source is preferably 1-50 L·min -1 kg -1 .
[0052] In step S3, the gas source for silicon deposition may further include an inert atmosphere.
[0053] Preferably, the inert atmosphere comprises one or more of nitrogen, helium, neon, argon, krypton and xenon.
[0054] Preferably, the volume ratio of the silicon source for the silicon deposition to the inert atmosphere is 1:(0.1-0.6), for example, 1:0.3.
[0055] In step S4, the carbon coating preferably includes the following steps: performing carbon deposition on the second precursor by chemical vapor deposition.
[0056] The carbon deposition temperature is preferably 500-1000°C, for example 600°C.
[0057] The carbon deposition time is preferably 1-5 hours, for example 2 hours.
[0058] The carbon source for carbon deposition may be a carbon source conventionally used for chemical vapor deposition in the art, preferably including one or more of methane, ethane, propane, acetylene, propyne, butyne and ethylene, such as methane.
[0059] In the process of carbon deposition, the ventilation rate of the carbon source is preferably 1-8 L·min -1 kg -1 .
[0060] Wherein, the gas source for carbon deposition may further include an inert atmosphere.
[0061] Preferably, the volume ratio of the carbon source for carbon deposition to the inert atmosphere is (3-5):1, for example, 4:1.
[0062] Preferably, the inert atmosphere comprises one or more of nitrogen, argon and helium.
[0063] In step S4, the pickling may be a pickling step conventionally performed in the art, preferably including a step of washing with hydrochloric acid; the mass ratio of the hydrochloric acid to the carbon-coated product is (5-50):1, for example 10:1; preferably, the concentration of the hydrochloric acid is 1-6 mol / L.
[0064] In step S4, the drying method may be a conventional drying method in the art, preferably spray drying or vacuum drying;
[0065] After step S2, preferably, the method further includes depositing lithium on the first precursor by chemical vapor deposition.
[0066] Preferably, the lithium source for lithium deposition may be a lithium source conventionally used for chemical vapor deposition in the art, preferably including organic lithium and / or inorganic lithium, more preferably organic lithium.
[0067] The inorganic lithium is, for example, lithium vapor.
[0068] The organic lithium preferably includes one or more of phenyl lithium, aryl lithium, aryl lithium, trialkyl lithium borohydride, vinyl lithium, α-lithium alkylphenyl sulfide and β-lithium enamine, for example, phenyl lithium.
[0069] Preferably, the temperature of the lithium deposition is 200-600°C.
[0070] Preferably, the lithium deposition time is 0.5-2 h, for example, 1 h.
[0071] Preferably, during the lithium deposition process, the ventilation rate of the lithium source is 1-5 L·min -1 kg -1 , for example, 3 L min -1 kg -1 .
[0072] Preferably, the gas source for lithium deposition also includes an inert atmosphere.
[0073] Further preferably, the volume ratio of the lithium source for lithium deposition and the inert atmosphere is (3-5):1, for example, 4:1.
[0074] Further preferably, the inert atmosphere comprises one or more of nitrogen, argon and helium.
[0075] The present invention provides a silicon-carbon material, which is prepared by the method for preparing the silicon-carbon material as described above.
[0076] The present invention provides a silicon-carbon material, which may include a core-shell structure, wherein the core-shell structure includes an inner core and an outer shell covering the inner core, wherein the inner core includes porous carbon, and along a direction away from the inner core, the outer shell includes a first carbon layer, a silicon layer, and a second carbon layer in sequence; wherein carbon nanotubes are distributed in at least one of the porous carbon, the first carbon layer, the silicon layer, and the second carbon layer.
[0077] Preferably, a lithium layer is further provided between the first carbon layer and the silicon layer.
[0078] Preferably, the distribution of the carbon nanotubes includes one or more of the following methods ①-⑦:
[0079] ① The carbon nanotubes are distributed inside the porous carbon;
[0080] ② The carbon nanotubes extend from the interior of the porous carbon and sequentially penetrate the first carbon layer, the silicon layer and the second carbon layer;
[0081] ③ The carbon nanotubes extend from the interior of the porous carbon and penetrate the first carbon layer and are embedded in the second carbon layer;
[0082] ④ The carbon nanotubes extend from the interior of the porous carbon and penetrate the first carbon layer, the silicon layer, and are embedded in the second carbon layer;
[0083] ⑤ The carbon nanotubes extend from the interior of the porous carbon and penetrate the first carbon layer and are embedded in the silicon layer;
[0084] ⑥ The carbon nanotubes extend from the inside of the first carbon layer and penetrate the second carbon layer;
[0085] ⑦ The carbon nanotubes extend from the inside of the first carbon layer and are embedded in the second carbon layer.
[0086] In the present invention, the carbon content of the silicon-carbon material may be 20%-80%, preferably 40%-50%, for example, 43.9%, 44%, 44.1%, 44.2%, 44.3%, 44.7%, 44.9%, 45.4%, 46.1%, 46.2%, 46.3% or 48.5%, where the percentage is the mass percentage of the silicon-carbon material.
[0087] In the present invention, the silicon content of the silicon-carbon material may be 20%-60%, preferably 45%-55%, for example, 46%, 46.7%, 50.1%, 51.5%, 51.7%, 51.8%, 51.9%, 52.1%, 52.3% or 53.1%, where the percentage is the mass percentage of the silicon-carbon material.
[0088] In the present invention, the nitrogen content of the silicon-carbon material may be 0.1%-1%, for example, 0.5%, 0.6%, 0.7%, 0.8% or 0.9%, where the percentage is the mass percentage of the silicon-carbon material.
[0089] In the present invention, the oxygen content of the silicon-carbon material may be 0.1%-0.5%, for example, 0.3% or 0.4%, where the percentage is the mass percentage of the silicon-carbon material.
[0090] In the present invention, the lithium content of the silicon-carbon material may be 0-10%, preferably 0.1%-5%, for example 0.3%, 0.4%, 0.5%, 0.6%, 0.9% or 4.9%, where the percentage is the mass percentage of the silicon-carbon material.
[0091] In the present invention, the specific surface area of the silicon-carbon material may be 1500-2500 m 2 / g, for example 1810m 2 / g.
[0092] In the present invention, the Dv50 particle size of the silicon-carbon material may be 4-20 μm, preferably 7.5-9 μm, for example, 7.8 μm, 8.0 μm, 8.1 μm, 8.2 μm, 8.3 μm or 8.5 μm.
[0093] In the present invention, the powder conductivity of the silicon-carbon material may be 1-200 S / m, preferably 28-96 S / m, for example, 28.7 S / m, 31.6 S / m, 39.7 S / m, 42.4 S / m, 43.2 S / m, 43.5 S / m, 44.3 S / m, 45.7 S / m, 48.6 S / m, 49.6 S / m, 54.8 S / m or 95.3 S / m.
[0094] In the present invention, the single particle strength of the silicon-carbon material may be 10-40 MPa, for example, 13.3 MPa, 14.3 MPa, 16.5 MPa, 17.5 MPa, 18.6 MPa, 19.3 MPa, 19.4 MPa, 21.3 MPa, 22.5 MPa, 24.3 MPa, 27.5 MPa or 35.4 MPa.
[0095] In the present invention, the silicon-carbon material satisfying the above-mentioned structure, composition and performance parameters can be prepared by the aforementioned method for preparing the silicon-carbon material.
[0096] The present invention also provides a pole piece, which comprises the silicon-carbon material as described above.
[0097] The present invention provides an application of the silicon-carbon material as described above as a negative electrode material in a lithium-ion battery.
[0098] The present invention also provides a lithium ion battery, which comprises the silicon-carbon material as described above.
[0099] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0100] The reagents and raw materials used in the present invention are commercially available.
[0101] The positive and progressive effects of the present invention are:
[0102] In the preparation method of the silicon-carbon material of the present invention, in the preparation of porous carbon, by introducing a transition metal salt, the transition metal salt can induce the carbon to grow carbon nanotubes in situ during the subsequent carbon deposition. The obtained silicon-carbon material has good electrical conductivity and compression resistance, and excellent expansion inhibition performance, and the prepared lithium-ion battery can take into account excellent first efficiency, gram capacity, rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0103] Figure 1 Schematic diagram of the structure of the silicon-carbon material obtained in Examples 1-13.
[0104] Reference numerals:
[0105] Porous Carbon 1
[0106] First carbon layer 2
[0107] Carbon Nanotubes 3
[0108] Silicon layer 4
[0109] Second carbon layer 5 DETAILED DESCRIPTION
[0110] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0111] In the following examples and comparative examples, the phenolic resin was purchased from Hubei Hengye Technology Co., Ltd., model 2135.
[0112] Example 1
[0113] S1. Preparation of porous carbon:
[0114] Add nickel nitrate to phenolic resin (the mass ratio of phenolic resin to nickel nitrate is 1:0.05) and mix well to obtain a mixture, heat it to 800°C at 5°C / min, keep it at 800°C for 2 hours, and then anneal it naturally to room temperature. After the above carbonization treatment, a precursor is obtained. The carbonized precursor is crushed to Dv50=8μm and then activated. Heat it to 600°C at 5°C / min, and introduce CO2 gas at 600°C with a ventilation volume of 5 L·min -1 kg -1 , activated for 4 h to obtain porous carbon;
[0115] S2. Carry out carbon deposition:
[0116] The porous carbon with uniformly distributed Ni particles was placed in a CVD device, argon was introduced as a protective gas, and the reactor was heated to 600°C. At atmospheric pressure, 4 L·min -1kg -1 Acetylene was introduced into the air at a rate of 15 L·min at atmospheric pressure for 30 min to grow carbon nanotubes in situ. -1 kg -1 While providing an inert protective gas into the reactor, the temperature is lowered to room temperature to obtain a first precursor uniformly doped with Ni, N, and carbon nanotubes;
[0117] After step S2, the first precursor is subjected to lithium deposition: the temperature is raised to 200°C, and the atmosphere is switched to phenyl lithium gas at a rate of 1 L min -1 kg -1 The ventilation rate is introduced, and the introduction is stopped after 1 hour, so that lithium is deposited on the first precursor;
[0118] S3, performing silicon deposition:
[0119] Monosilane / nitrogen (volume ratio 1:0.3) was introduced for 3 h at 600 °C to deposit silicon to obtain the second precursor; wherein the flow rate of the mixed gas of monosilane and nitrogen was 30 L min -1 kg -1 ;
[0120] S4, carbon coating:
[0121] Under nitrogen atmosphere, control the CVD equipment at 600°C, switch the atmosphere to carbon source acetylene, carbon-coat the second precursor for 2 hours, and cool down;
[0122] Pickling: Pickling is performed several times with 1 mol / L hydrochloric acid. The mass ratio of hydrochloric acid to the carbon-coated product is 10:1 in each pickling. The material is washed until no transition metal exists on the surface of the material and the magnetic foreign matter impurities are below 10 ppm.
[0123] Drying: The acid-washed product was mixed with deionized water of 10 times its mass, and then spray-dried to obtain a silicon-carbon material with a Dv50 particle size of 7.8 μm.
[0124] Example 2
[0125] The difference between this embodiment and embodiment 1 is that after step S2, when lithium deposition is performed on the first precursor, only the ventilation rate of phenyllithium gas is changed to 3 L L·min -1 kg -1 , the remaining steps are the same as those in Example 1.
[0126] Example 3
[0127] The difference between this embodiment and embodiment 1 is that after step S2, when lithium deposition is performed on the first precursor, only the ventilation rate of phenyllithium gas is changed to 5 L·min -1 kg-1 g, the remaining steps are the same as in Example 1.
[0128] Example 4
[0129] The difference between this embodiment and embodiment 2 is that in step S2, when carbon deposition is performed, only the ventilation rate of acetylene is changed to 1 L·min -1 kg -1 , the remaining steps are the same as those in Example 2.
[0130] Example 5
[0131] The difference between this embodiment and embodiment 2 is that in step S2, when carbon deposition is performed, only the ventilation rate of acetylene is changed to 8 L·min -1 kg -1 , the remaining steps are the same as those in Example 2.
[0132] Example 6
[0133] The difference between this embodiment and embodiment 2 is that in step S1, only the mass ratio of phenolic resin to nickel nitrate is changed to 1:0.3, and the remaining steps are the same as those in embodiment 2.
[0134] Example 7
[0135] The difference between this embodiment and embodiment 2 is that in step S1, only the mass ratio of phenolic resin to nickel nitrate is changed to 1:0.8, and the remaining steps are the same as those in embodiment 2.
[0136] Example 8
[0137] The only difference between this embodiment and embodiment 2 is that after step S2, lithium deposition is not performed on the first precursor, and the remaining steps are the same as those in embodiment 2.
[0138] Example 9
[0139] The difference between this embodiment and embodiment 2 is that in step S1, nickel sulfate is used to replace nickel nitrate, and the ratio of phenolic resin to nickel sulfate is 1:0.05. The remaining steps are the same as those in embodiment 2.
[0140] Example 10
[0141] The difference between this embodiment and embodiment 2 is that in step S1, nickel phosphate is used to replace nickel nitrate, and the ratio of phenolic resin to nickel phosphate is 1:0.05. The remaining steps are the same as those in embodiment 2.
[0142] Embodiment 11
[0143] The difference between this embodiment and embodiment 2 is that in step S1, nickel borate is used to replace nickel nitrate, and the ratio of phenolic resin to nickel borate is 1:0.05. The remaining steps are the same as those in embodiment 2.
[0144] Example 12
[0145] The difference between this embodiment and embodiment 2 is that in step S1, ferric nitrate is used to replace nickel nitrate, and the ratio of phenolic resin to ferric nitrate is 1:0.05. The remaining steps are the same as those in embodiment 2.
[0146] Example 13
[0147] The difference between this embodiment and embodiment 2 is that in step S1, tin nitrate is used to replace nickel nitrate, and the ratio of phenolic resin to tin nitrate is 1:0.05. The remaining steps are the same as those in embodiment 2.
[0148] The schematic diagram of the structure of the silicon-carbon material obtained in Examples 1-13 is as follows Figure 1 As shown. The silicon-carbon material includes a core-shell structure, which includes a core and a shell covering the core; the core includes porous carbon 1, and the shell includes a first carbon layer 2, a silicon layer 4, and a second carbon layer 5 in a direction away from the core, and carbon nanotubes 3 are distributed in at least one of the porous carbon 1, the first carbon layer 2, the silicon layer 4, and the second carbon layer 5. In addition, Figure 1 The middle green spheres are schematic locations of transition metal salts. During the acid washing process, most of the transition metal salts have actually been washed away.
[0149] Comparative Example 1
[0150] The difference between this comparative example and Example 2 is that in step S1, nickel nitrate is not added, carbon nanotubes are directly added, and there is no step S2 (the first vapor deposition is not used for carbon deposition), and the remaining steps are the same as Example 2.
[0151] Comparative Example 2
[0152] The only difference between this comparative example and Example 2 is that in step S1, nickel nitrate is not added, and the remaining steps are the same as those in Example 2.
[0153] Comparative Example 3
[0154] The difference between this comparative example and Example 2 is that there is no step S2, that is, no carbon deposition is performed on the porous carbon, and the remaining steps are the same as those in Example 2.
[0155] Effect Example 1
[0156] The porous carbon and silicon-carbon materials prepared in Examples 1-13 and Comparative Examples 1-3 were tested as follows:
[0157] (1) Specific surface area: calculated using an eight-station specific surface area analyzer (model NT-8000) to characterize the entire pore.
[0158] (2) Pore volume, micropore volume ratio and mesopore volume ratio: calculated after characterizing the entire pore using an eight-station surface area analyzer (model NT-8000). After calculating the volume occupied by pores between 0.7 nm and 50 nm, the micropore volume ratio was calculated using the micropore volume / pore volume ratio, and the mesopore volume ratio was calculated using the mesopore volume / pore volume ratio.
[0159] (3) Dv50 particle size: Add 0.02 g of silicon-carbon material to a 50 mL clean beaker, add 20 mL of deionized water, and use a 120 W ultrasonic cleaner for 5 min to completely disperse the silicon-carbon material in the deionized water to obtain a dispersion. Use a particle size analyzer (MasterSizer 2000) to test the above dispersion to obtain the Dv50 particle size of the silicon-carbon material.
[0160] (4) Silicon content, lithium content, nickel content, iron content and tin content: ICP (model: Thermofisher ICAP 7400 DUO) was used to test the contents of the above elements. The sample preparation method was: 20 mL of aqua regia was used to dissolve 3 g of silicon-carbon material for testing.
[0161] (5) Test the oxygen content in the material using a carbon oxygen analyzer.
[0162] (6) Carbon content: Characterized and calculated using the SEM energy spectrum.
[0163] (7) Nitrogen content: tested using Shanghai Baoying TC-306 oxygen and nitrogen analyzer.
[0164] (8) Oxygen content: tested using Shanghai Baoying TC-306 oxygen and nitrogen analyzer.
[0165] (9) Single particle strength: The test was conducted using the Yuanneng Technology single particle mechanical properties testing system SPFT2000.
[0166] (10) Powder conductivity:
[0167] The powder resistivity test equipment PRCD3100 of Yuanneng Technology was used to test the powder conductivity of silicon-carbon materials with the help of a resistivity tester and an electronic pressure tester. The correction coefficient F of the resistivity tester was set to 1, and the powder conductivity test mold was placed on the table of the electronic pressure tester. After the pressure was increased to 1000kg, the displacement and deformation were cleared. 0.5g of silicon-carbon material powder was added to the test mold, and the upper gasket was added after vibrating for 10 seconds. The test mold was placed on the table of the electronic pressure tester and connected to the resistivity tester. The electronic pressure tester was pressurized to 5MPa, kept at a constant pressure for 60s, and then the pressure was released to zero. The sample deformation height and the value of the resistivity tester were read as (sample resistance). The powder conductivity is calculated according to the following formula: σ=h / (S×R) ×100, where: σ is the powder conductivity of the silicon-carbon material, in S / m, h is the sample deformation height, in cm, and S is the sample bottom area, which is 3.14cm 2 , R is the sample resistance, in Ω.
[0168] The above test results are shown in Table 1 and Table 2.
[0169] Effect Example 2
[0170] Preparation of pole pieces and lithium-ion batteries
[0171] This effect embodiment is to assemble the carbon silicon materials provided in Examples 1-13 and Comparative Examples 1-3 as negative electrode materials into a lithium ion battery, and the specific steps are as follows:
[0172] (1) Preparation of pole pieces: Silicon carbon material, conductive agent (Super-P), and polyacrylic acid (PAA) binder were mixed in a mass ratio of 80:10:10 to prepare a slurry. After stirring and mixing, the slurry was coated on the copper foil current collector. After drying at room temperature, the slurry was placed in a vacuum oven and further dried at 60°C for 12 h to obtain a pole piece.
[0173] (2) Lithium-ion battery assembly: The electrode obtained above was cut into a circular electrode with a diameter of 10 mm and an active material loading of 1.3 mg / cm 2 ;Metallic lithium sheet as counter electrode;
[0174] Electrolyte formula: 1 mol / L LiPF6 (the solvent is a mixed solvent of ethylene carbonate and diethyl carbonate with a volume ratio of 1:1, and 5% volume percentage of fluoroethylene carbonate based on the mixed solvent is added) as the electrolyte;
[0175] Adopt polypropylene microporous diaphragm;
[0176] The cells were assembled into 2032-type button cells in an argon atmosphere glove box; 50 μL of electrolyte was added to each cell.
[0177] Electrochemical performance test
[0178] The electrical performance of the button cell prepared above was tested:
[0179] The charge and discharge cut-off voltages were 1.5V and 0.005V, respectively, and activation was performed at a rate of 0.05C;
[0180] Then the charge and discharge cycle tests were carried out at 0.1C, 0.5C and 1C rates, as follows:
[0181] (1) The amount of electrode expansion under full charge: (thickness of electrode after saturated lithium insertion - thickness of copper foil) / (thickness of electrode without lithium insertion - thickness of copper foil) - 1.
[0182] (2) 300-cycle capacity retention rate (%): Use a current of 0.5C and cycle within a voltage window of 0-1.5V. Calculate the 300-cycle capacity retention rate (%) using the discharge capacity at the 300th cycle / the capacity at the first cycle × 100.
[0183] (3) 1.5V gram capacity:
[0184] First, assemble a CR2032 button battery, then use constant voltage discharge mode, discharge at 0.1V / h to 0.000V, charge at 0.1V / h to 1.5V, record the 0.1C current of the charging capacity, reassemble a CR2032 button battery, perform constant current charge and discharge test with 0.1C current recording the charging capacity, discharge to 0V and then charge to 1.5V, after obtaining the capacity, use the method of capacity / mass of active material in the electrode to obtain the gram capacity of 0.1C 1.5V, where the mass of active material = mass of silicon-carbon material.
[0185] (4) First efficiency (%): lithium removal capacity of the first cycle / lithium insertion capacity × 100.
[0186] (5) Ratio retention rate:
[0187] 1C 1.5V cycle failure number (at 25℃): First assemble a CR2032 button battery, then discharge it at a constant voltage rate of 0.1V / h to 0.000V, then charge it at 0.1V / h to 1.5V, record the charging capacity, reassemble a CR2032 button battery, and perform a constant current charge and discharge test at a 1C current with the charging capacity recorded, repeatedly charge and discharge from 0V to 1.5V, record the discharge capacity, terminate when the discharge capacity is 60% of the 1C 1.5V capacity, and record the number of cycles.
[0188] 0.5C 1.5V cycle failure number (at 25℃): First assemble a CR2032 button battery, then use constant voltage discharge method, discharge it to 0.000V at 0.1V / h, then charge it to 1.5V at 0.1V / h, record the charging capacity, reassemble a CR2032 button battery, and perform constant current charge and discharge test with 0.5C current to record the charging capacity, repeatedly charge and discharge from 0V to 1.5V, record the discharge capacity, terminate when the discharge capacity is 60% of the 0.5C 1.5V capacity, and record the number of cycles.
[0189] Rate retention rate = 1C 1.5V cycle failure number / 0.5C 1.5V cycle failure number.
[0190] The above test results are shown in Table 3.
[0191]
[0192]
[0193]
[0194] Note: “ / ” in Table 1 and Table 2 means that the condition parameter is not involved in the specific experiment.
[0195] The powder conductivity of the silicon-carbon material obtained in Examples 1-13 of the present invention can reach more than 28 S / m, and the single particle strength can reach more than 13MPa. The silicon-carbon material has excellent conductivity and mechanical strength, and has excellent expansion inhibition performance. The first efficiency of the lithium-ion battery prepared using the above silicon-carbon material as the negative electrode material can reach more than 89%, and the rate retention rate can reach more than 0.65. On this basis, the 1.5V gram capacity can reach more than 1800 mAh / g, and the 300-cycle cycle capacity retention rate can reach more than 44%. The expansion of the pole piece in the fully charged state can be less than 91%.
[0196] The present invention introduces transition metal salts when preparing porous carbon, and in-situ grows carbon nanotubes during the subsequent carbon deposition. The obtained silicon-carbon material can have both excellent conductivity and mechanical strength, and excellent expansion inhibition performance. The prepared lithium-ion battery can have both excellent first efficiency and rate retention rate. However, directly adding carbon nanotubes, or not introducing transition metal salts, or not performing the first vapor phase deposition, it is impossible to achieve the above-mentioned effects.
[0197] Compared with Example 2, in Comparative Example 1, no transition metal salt was added, but carbon nanotubes were directly added. The first efficiency, rate retention rate, 1.5V gram capacity, 300 cycle capacity retention rate and pole piece expansion under full charge state of the lithium ion battery obtained by using the silicon-carbon material as the negative electrode material were significantly deteriorated. This may be because the in-situ grown carbon nanotubes are more uniform than the doped carbon nanotubes, and will not produce agglomeration to affect dispersion, and the contact with the carbon material obtained by the phenolic resin is higher. When the carbon nanotubes are directly added, the phenolic resin will shrink during carbonization, resulting in poor contact between the phenolic resin and the directly added carbon nanotubes.
[0198] Compared with Example 2, in Comparative Example 2, only the transition metal salt is not added. Although the prepared lithium-ion battery has a higher 1.5V gram capacity and 300 cycle capacity retention rate, the first efficiency is reduced, the rate retention rate is greatly reduced, and the expansion of the electrode in the fully charged state is significantly increased.
[0199] Compared with Example 2, in Comparative Example 3, there is no step S2 (the first vapor deposition is not performed), and the first efficiency, rate retention rate, 1.5V gram capacity, 300 cycle capacity retention rate and electrode expansion amount of the lithium-ion battery in the fully charged state are significantly deteriorated.
[0200] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing a silicon-carbon material, characterized in that: It includes the following steps: S1, carbonizing and activating a mixture of a carbon source and a transition metal salt to obtain porous carbon; S2, performing carbon deposition on the porous carbon by chemical vapor deposition to in-situ grow carbon nanotubes to obtain a first precursor; S3, performing silicon deposition on the first precursor by chemical vapor deposition to obtain a second precursor; S4, carbon coating the second precursor; After acid washing and drying, the silicon-carbon material is obtained.
2. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the mass ratio of the carbon source to the transition metal salt is 1:(0.01-0.8), preferably 1:(0.05-0.8), for example 1:0.05, 1:0.3 or 1:0.8; And / or, in step S1, the transition metal salt includes one or more of transition metal nitrates, transition metal sulfates, transition metal phosphates and transition metal borates; Preferably, the transition metal salt comprises nickel nitrate; Preferably, the transition metal salt comprises nickel sulfate; Preferably, the transition metal salt comprises nickel phosphate; Preferably, the transition metal salt comprises nickel borate; Preferably, the transition metal salt comprises tin nitrate; And / or, in step S1, the transition metal salt includes one or more of iron salt, nickel salt, cobalt salt, silver salt, gold salt and tin salt, for example, nickel salt or tin salt; And / or, in step S1, the carbon source comprises one or more of resin, sucrose, glucose, fructose, starch, cellulose, triglyceride, fatty acid, hemicellulose, lignin and asphalt, preferably resin, more preferably phenolic resin; And / or, in step S1, the temperature of the carbonization treatment is 400-800°C; And / or, in step S1, the carbonization treatment time is 1-8 h, for example, 2 h; And / or, in step S1, the heating rate of the carbonization treatment is 1-8°C / min, for example, 5°C / min; And / or, in step S1, the carbonization treatment is carried out by heating the temperature to 400-800°C at 1-8°C / min and keeping the temperature for 1-8 hours, for example, heating the temperature to 800°C at 5°C / min and keeping the temperature for 2 hours; And / or, in step S1, the activation treatment includes alkali activation or gas activation; the gas activation is preferably carbon dioxide activation or water vapor activation; Wherein, the gas activation time is preferably 1-8 hours, for example 4 hours; Wherein, the temperature of the gas activation is preferably 500-600°C; Wherein, the heating rate of the gas activation is preferably 1-8°C / min, for example, 5°C / min; The ventilation volume of the gas activation is preferably 1-6 L·min -1 kg -1 , for example, 5 L min -1 kg -1 ; The gas activation method is preferably: heating to 500-600°C at 1-8°C / min and keeping warm for 1-8 hours, for example: heating to 600°C at 5°C / min and keeping warm for 4 hours; And / or, in step S1, the activation treatment further includes a crushing treatment; the crushing treatment is preferably crushed to a Dv50 particle size of 5-15 μm, for example, 8 μm; And / or, in step S1, the Dv50 particle size of the porous carbon is 5-15 μm, preferably 7-8 μm, for example, 7.7 μm, 7.8 μm or 7.9 μm; And / or, in step S1, the specific surface area of the porous carbon is 1200-2500 m 2 / g, preferably 1800-1950 m 2 / g, for example, 1810 m 2 / g, 1854 m 2 / g, 1867 m 2 / g, 1869 m 2 / g, 1876 m 2 / g, 1886 m 2 / g, 1896 m 2 / g or 1945 m 2 / g; And / or, in step S1, the pore volume of the porous carbon is 0.7-1.5 cm 3 / g, for example, 0.87 cm 3 / g, 0.98 cm 3 / g, 1.01 cm 3 / g, 1.05 cm 3 / g, 1.08 cm 3 / g, 1.09 cm 3 / g, 1.1 cm 3 / g or 1.11 cm 3 / g; And / or, in step S1, the mesopore volume of the porous carbon is 0-20%, preferably 5%-15%, for example, 5.8%, 6.8%, 8.6%, 9.8%, 10.5%, 10.8%, 12.4%, 14.6% or 14.7%; And / or, in step S1, the micropore volume of the porous carbon is 80-100%, preferably 85%-95%, for example, 85.3%, 85.4%, 87.6%, 89.2%, 89.5%, 90.2%, 91.4%, 93.2% or 94.2%.
3. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S2, the temperature of the carbon deposition is 400-800°C, for example, 600°C; And / or, in step S2, the carbon deposition time is 10-60 min, for example, 30 min; And / or, in step S2, the carbon source for carbon deposition includes one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates, more preferably includes one or more of methane, ethane, propane, cyclopropane, n-butane, isobutane, n-pentane, neopentane, methyl chloride, ethyl chloride, trifluoromethane, ethylene oxide, acetylene, propyne, butyne, methylacetylene, vinylacetylene and ethylene, such as methane or acetylene; And / or, in step S2, during the carbon deposition process, the ventilation rate of the carbon source is preferably 1-8 L·min -1 kg -1 , for example 4 L·min -1 kg -1 or 5 L min -1 kg -1 ; and / or, in step S2, the gas source for carbon deposition further comprises an inert atmosphere; Preferably, the volume ratio of the carbon source of the carbon deposition to the inert atmosphere is 1:(0.5-15); Preferably, the inert atmosphere comprises one or more of nitrogen, argon and helium; Preferably, the ventilation volume of the inert atmosphere is 10-50 L·min -1 kg -1 , for example, 15 L min -1 kg -1 .
4. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S3, the temperature of silicon deposition is 300-1000° C., for example, 600° C.; And / or, in step S3, the silicon deposition time is 1-6 hours, for example, 3 hours; And / or, in step S3, the silicon source for the silicon deposition includes one or more of monosilane, disilane, trisilane, dimethylsilane, hexamethyldisilane, dichlorodihydrosilane, trichlorosilane, silicon tetrachloride and silicon tetrafluoride, for example, monosilane; And / or, in step S3, during the silicon deposition process, the ventilation rate of the silicon source is 1-50 L·min -1 kg -1 ; And / or, in step S3, the gas source for silicon deposition preferably also includes an inert atmosphere; Preferably, the inert atmosphere comprises one or more of nitrogen, helium, neon, argon, krypton and xenon; Preferably, the volume ratio of the silicon source for silicon deposition to the inert atmosphere is 1:(0.1-0.6), for example, 1:0.3; And / or, in step S4, the carbon coating comprises the following steps: performing carbon deposition on the second precursor by chemical vapor deposition; Wherein, the temperature of the carbon deposition is preferably 500-1000°C, for example 600°C; Wherein, the carbon deposition time is preferably 1-5 hours, for example, 2 hours; Wherein, the carbon source of the carbon deposition preferably includes one or more of methane, ethane, propane, acetylene, propyne, butyne and ethylene, for example, methane; In the process of carbon deposition, the ventilation rate of the carbon source is preferably 1-8 L·min -1 kg -1 ; And / or, in step S4, the pickling comprises a step of washing with hydrochloric acid; the mass ratio of the hydrochloric acid to the carbon-coated product is (5-50):1, for example, 10:1; preferably, the concentration of the hydrochloric acid is 1-6 mol / L; And / or, the drying method is spray drying or vacuum drying.
5. The method for preparing the silicon-carbon material according to claim 1, characterized in that: After step S2, the method further includes depositing lithium on the first precursor by chemical vapor deposition; Preferably, the lithium source for lithium deposition includes organic lithium and / or inorganic lithium, more preferably organic lithium; wherein the inorganic lithium is, for example, lithium vapor; the organic lithium preferably includes one or more of phenyl lithium, aryl lithium, aryl lithium, trialkyl lithium borohydride, vinyl lithium, α-lithium alkylphenyl sulfide and β-lithium enamine, for example, phenyl lithium; Preferably, the temperature of the lithium deposition is 200-600°C; Preferably, the lithium deposition time is 0.5-2 h, for example, 1 h; Preferably, during the lithium deposition process, the ventilation rate of the lithium source is 1-5 L·min -1 kg -1 , for example, 3 L min -1 kg -1 ; Wherein, the gas source for lithium deposition preferably also includes an inert atmosphere; Preferably, the volume ratio of the lithium source for lithium deposition and the inert atmosphere is (3-5):1, for example, 4:1; Preferably, the inert atmosphere comprises one or more of nitrogen, argon and helium.
6. A silicon-carbon material, characterized in that: The silicon-carbon material is prepared by the method for preparing the silicon-carbon material according to any one of claims 1 to 5.
7. A silicon-carbon material, characterized in that: The silicon-carbon material includes a core-shell structure, which includes an inner core and an outer shell covering the inner core, wherein the inner core includes porous carbon, and along a direction away from the inner core, the outer shell includes a first carbon layer, a silicon layer, and a second carbon layer in sequence; wherein carbon nanotubes are distributed in at least one of the porous carbon, the first carbon layer, the silicon layer, and the second carbon layer.
8. The silicon-carbon material according to claim 7, characterized in that: A lithium layer is also provided between the first carbon layer and the silicon layer; And / or, the distribution of the carbon nanotubes includes one or more of the following methods ①-⑦: ① The carbon nanotubes are distributed inside the porous carbon; ② The carbon nanotubes extend from the interior of the porous carbon and sequentially penetrate the first carbon layer, the silicon layer and the second carbon layer; ③ The carbon nanotubes extend from the interior of the porous carbon and penetrate the first carbon layer and are embedded in the second carbon layer; ④ The carbon nanotubes extend from the interior of the porous carbon and penetrate the first carbon layer, the silicon layer, and are embedded in the second carbon layer; ⑤ The carbon nanotubes extend from the interior of the porous carbon and penetrate the first carbon layer and are embedded in the silicon layer; ⑥ The carbon nanotubes extend from the inside of the first carbon layer and penetrate the second carbon layer; ⑦ The carbon nanotubes extend from the inside of the first carbon layer and are embedded in the second carbon layer; and / or, the carbon content of the silicon-carbon material is 20%-80%, preferably 40%-50%, for example, 43.9%, 44%, 44.1%, 44.2%, 44.3%, 44.7%, 44.9%, 45.4%, 46.1%, 46.2%, 46.3% or 48.5%; and / or, the silicon carbon material has a silicon content of 20%-60%, preferably 45%-55%, for example, 46%, 46.7%, 50.1%, 51.5%, 51.7%, 51.8%, 51.9%, 52.1%, 52.3% or 53.1%; And / or, the nitrogen content of the silicon-carbon material is 0.1%-1%, for example, 0.5%, 0.6%, 0.7%, 0.8% or 0.9%; And / or, the oxygen content of the silicon-carbon material is 0.1%-0.5%, for example, 0.3% or 0.4%; And / or, the lithium content of the silicon-carbon material is 0-10%, preferably 0.1%-5%, for example 0.3%, 0.4%, 0.5%, 0.6%, 0.9% or 4.9%; And / or, the specific surface area of the silicon-carbon material is 1500-2500 m 2 / g, for example, 1810m 2 / g; And / or, the Dv50 particle size of the silicon-carbon material is 4-20 μm, preferably 7.5-9 μm, for example, 7.8 μm, 8.0 μm, 8.1 μm, 8.2 μm, 8.3 μm or 8.5 μm; And / or, the 5 MPa powder conductivity of the silicon-carbon material is 1-200 S / m, preferably 28-96 S / m, for example, 28.7 S / m, 31.6 S / m, 39.7 S / m, 42.4 S / m, 43.2 S / m, 43.5 S / m, 44.3 S / m, 45.7 S / m, 48.6 S / m, 49.6 S / m, 54.8 S / m or 95.3 S / m; And / or, the single particle strength of the silicon-carbon material is 10-40 MPa, for example, 13.3 MPa, 14.3 MPa, 16.5 MPa, 17.5 MPa, 18.6 MPa, 19.3 MPa, 19.4 MPa, 21.3 MPa, 22.5 MPa, 24.3 MPa, 27.5 MPa or 35.4 MPa.
9. Use of the silicon-carbon material as claimed in any one of claims 6 to 8 as a negative electrode material in a lithium-ion battery.
10. A lithium ion battery, characterized in that: It comprises the silicon-carbon material as described in any one of claims 6-8.
Citation Information
Cited By
Preparation method of carbon-silicon negative electrode material
CN120518082A
A method for preparing carbon-silicon negative electrode material
CN120518082B
Preparation method of improved silicon-carbon composite negative electrode material and lithium ion battery
CN120887407A
Porous carbon particle and preparation method thereof, negative electrode active material and secondary battery
CN121282198A